Skrining Resep untuk Identifikasi Interaksi Obat pada Pasien Diabetes Melitus dan Hiperurisemia Periode Oktober 2023 hingga Maret 2024 di Rumah Sakit Advent - Surbekti , Destiana Tata; Sembiring, Novitaria Br; Lubis, Asyrun Alkhairi (Journal of Pharmaceutical and Sciences, 2025)
Background: Diabetes mellitus (DM) and hyperuricemia are frequently encountered comorbidities in clinical practice with increasing prevalence. Long-term pharmacological therapy for these conditions carries the potential for drug interactions and other drug-related problems. Prescription completeness evaluation and drug interaction identification are necessary to ensure therapeutic safety and efficacy. Objectives: This study aimed to identify medications prescribed for patients with DM and hyperuricemia, evaluate potential drug interactions, and assess prescription completeness based on administrative standards according to Indonesian Ministry of Health Regulation No. 72 of 2016. Methods: This retrospective descriptive study with a cross-sectional design analyzed 50 outpatient prescriptions at Advent Hospital Medan from October 2023 to March 2024. The analysis covered administrative, pharmaceutical, and clinical aspects. Drug interactions were identified using Drugs.com with classification as major, moderate, and minor. Results: The most frequently prescribed antidiabetic drugs were metformin (82%), glimepiride (76%), and acarbose (64%), while for hyperuricemia they were allopurinol (88%) and meloxicam (72%). Ten drug interactions were identified, consisting of 8 moderate (80%), 1 major (10%), and 1 minor (10%). Administrative evaluation showed 92% completeness for mandatory components, but patient weight (48%), physician address (64%), and physician phone number (56%) were frequently omitted. Conclusion: The study revealed a significant prevalence of moderate drug interactions between antidiabetic drugs and non-steroidal anti-inflammatory drugs (NSAIDs). Optimization of prescription screening systems and completion of patient clinical data are required to enhance therapy safety.